The perception of foreign language students toward the implementation of inclusive education - Cahya Kusuma Negara; Dewa Ayu Eka Agustini; Luh Diah Surya Adnyani (Universitas Islam Malang, 2021)
This research aimed to describe the implementation of inclusive education and identify the challenges students might have in English courses at SMK N 3 Singaraja. The research subjects were students with disabilities and regular students who studied at XI MM 2 (Multi-media). This research was a case study that used the descriptive qualitative method. The data collection was done by conducting a questionnaire and interview guide sequentially. The student's perception was measured from 3 aspects, namely perceiver, target, and social setting. The result from the questionnaire and interview was analyzed continuously and described descriptively. This research showed that students with disabilities and regular students have a good perception of inclusive education implementation. However, there were several challenges, such as lacking adaptation with inclusive classrooms, time, facilities, and special teachers. It implied that the teacher and school's staff should give examples, more chances, and more attention to the inclusive class students.